Cardiorenal Syndrome in COVID-19 Patients: A Systematic Review - Lin, Ling; Chen, Yangqin; Han, Dongwan; Yang, Andrew; Wang, Amanda Y.; Qi, Wenjie (Frontiers in Cardiovascular Medicine, 2022)
Aims: To perform a systematic review assessing the clinical manifestations and outcomes of cardiorenal syndrome or the presence of both cardiac and renal complications in t he 2019 coronavirus disease (COVID-19) patients. Methods: All relevant studies about cardiorenal syndrome or both cardiac and renal complications in COVID-19 patients were retrieved on PUBMED, MEDLINE and EMBASE from 1 Dec 2019 to 20 Feb 2022. Results: Our search identified 15 studies including 637 patients with a diagnosis of cardiorenal syndrome or evidence of both cardiac and renal complications followingSARS-CoV-2 infection.They were male predominant (66.2%, 422/637), with a mean age of 58 years old. Cardiac complications included myocardial injury (13 studies), heart failure (7 studies), arrhythmias (5 studies), or myocarditis and cardiomyopathy (2 studies). Renal complications manifested as acute kidney injury with or without oliguria. Patients with cardiorenal injury were often associated with significantly elevated levels of inflammatory markers (CRP, PCT, IL-6). Patients with a diagnosis of cardiorenal syndrome or evidence of both cardiac and renal complications had more severe disease and poorer prognosis (9 studies). Conclusion: The presence of either cardiorenal syndrome or concurrent cardiac and renal complications had a significant impact on the severity of disease and a mortality rate among patients with COVID-19 infection. Therefore careful assessment and management of potential cardiac and renal complications in patients with covid-19 infection are important to improve their outcomes.